PENGARUH KEBIASAAN MEROKOK DAN OLAH RAGA TERHADAP KAPASITAS VITAL PARU (STUDI PADA KARYAWAN UNIVERSITAS DIAN NUSWANTORO SEMARANG TAHUN 2010) - Nurjanah Nurjanah; Suharyo Suharyo (VISIKES: Jurnal Kesehatan Masyarakat, 2013)
Background: One indicator of the health workforce is the lung function as an oxygen supplier organ for energy supply and metabolism. The presurvey show many employees smoke indoor, while campus must be a smoke free area. Therefore, this research will explain how the influence of smoking habits and exercise of pulmonary vital capacity of Udinus employees.Method: this is survey with cross sectional approach, conducted in May-July 2010 with measurement by spyrometre and interviews. The sample is Udinus employee, amount of 33 respondents. Data analysis using chi-square test.Result: there is no correlation between smoking status with pulmonary vital capacity (pvalue 0.188), because non-smoking employees exposed environmental tobacco smoke from the indoor smoker and there is no correlation between exercise habits with pulmonary vital capacity (p-value 0.465) because the sports habit is inadequate.